Anisotropic Conformal Model in $f(R, φ)$ Theory - Doğukan Taşer (Journal of New Theory)
In this study, we examine conformal spherically symmetric spacetime with anisotropic fluid in $f(R,ϕ)$ theory. The exact solutions of field equations are obtained for $f(R,ϕ)=(1+λη^2 ϕ^2 )R$ model. All the quantities for anisotropic fluid are investigated through equation of state constant, $ω$. The models for three different selections of $ω$ are represented for the constructed model. Moreover, string gas is the only condition that anisotropic fluid behaves as an isotropic fluid for the constructed model. Furthermore, the anisotropy parameter and causality conditions are examined. Lastly, the results for the solutions are concluded from the physical and geometrical viewpoint.